Analisis Strategi Pemenangan Alfiansyah Bustami “Komeng” Dalam Pemilihan Anggota DPD Jawa Barat Tahun 2024 - Aliah, Shilmi Ainun; Purwanto, Calista Sahlah; Fajri, Nadhira Nurul; Ahmad, Fauzan Ramdhani; Aji, Muhammad Prakoso (Universitas Medan Area, 2024)
This article analyzes the winning strategy of Alfiansyah Bustami, known as “Komeng,” in the election for the West Java DPD in 2024. This research aims to identify the approaches used by Komeng in attracting voter support, including using social media, mobilizing the mass base, and collaborating with various communities. The method used is qualitative analysis with data collection through interviews, observation, and document review. The results show that effective communication strategies such as creating “anti-mainstream” and humorous branding, using photos that are different from other candidates during elections, direct involvement with the community, and utilization of local issues by exposing his visions regarding the preservation of relevant arts and culture are the keys to success in Komeng's campaign. This research provides limitations regarding Komeng's strategy for winning the election without conducting a traditional campaign. The findings are expected to offer insights to other legislative candidates in designing effective campaign strategies and enrich the literature on local politics in Indonesia.